STAT3: A Molecular Target for Cancer Whose Time Has Come - Barton, Beverly E. (Current Signal Transduction Therapy, 2006)
Signal transducer and activator of transcription (STAT) proteins are latent cytoplasmic proteins that transmit cell-surface signals generated by ligand-receptor interactions to the nucleus. They are activated mainly by phosphorylation. Of the STAT proteins, STAT3 and to a lesser extent STAT5, is associated with transformed cells, particularly in tumors arising from oncogenes that activate tyrosine kinase signaling pathways. In benign cells, STAT3 like other STAT proteins, is transiently activated then deactivated by multiple regulatory proteins. However, in many malignant cells, the activation of STAT3 is constitutive; this persistent and aberrant signaling by STAT3 results in the continued expression of anti-apoptotic genes of the bcl family and of survivin, cell-cycling genes, angiogenic factors such as VEGF, and metastasis-promoting factors such as matrix metalloproteases. The activity of some oncogenic viral proteins, notably v-src, is due to persistent activation of STAT3. When malignant cells express constitutive STAT3 activation, their very survival depends upon STAT3's continued activation or expression or DNA-binding activity; inhibiting STAT3 at any of these steps results in cancer cell apoptosis, whereas benign cells survive the same treatment. This review will discuss the critical role of persistent STAT3 in the maintenance of the malignant state, and the efforts published to date for inhibiting STAT3 as a future therapeutic approach for cancer treatment; limitations of each inhibitory strategy will be included in so far as information is available.
Keywords: phosphotyrosyl peptide